Pemberdayaan Kelompok PKK dalam Pengelolaan Limbah Minyak Goreng Bekas Berbasis Ecogreen - Agustikawati, Nurlaila; Riyadi, Anak Agung Ngurah Ketut; Hamid, Abdul (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to improve the skill of the PKK group in Labuhan Sumbawa Village in processing used oil waste based on eco-green. The method of this community service activity is carried out by FGD, counseling, and training. The evaluation instrument uses a questionnaire and is analyzed using the chi-square analysis technique. The results of this community service activity are increased knowledge of partners who can form a positive attitude about the processing of used oil waste. This can be seen from the significant difference in the attitudes of partners before and after counseling on the management of used oil waste (P value <0.05). In addition, there is an increase in partner skills in managing used oil waste in aromatherapy candles.